Diagnóstico de risco ambiental em áreas de vulnerabilidade da cidade de Marília (SP) - Cardoso, Laila Regina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The dilemma in the present moment of our society is the challenge of keeping up the development of new technologies and that is in a sustainable manner, however also entails the development impacts. Along with development comes the overcrowded cities, causing damage to both the environment as for society, by making studies on this topic and consecutively as related environmental vulnerability and risk required. This study aims to understand the issue of vulnerability to environmental hazards in urban areas, analyzing these risks due to climate variability and perception of environmental risks by the residents of vulnerable neighborhoods the city of Marília (SP). To conduct the survey was conducted literature concerning the topic and subsequently for the delimitation of the study area within the city of Marília ( SP ) were made interpolation data Social Exclusion, Municipal Director Plan, Local Plan Social Housing, Civil Defense, reaching some neighborhoods in two regions ( Northeast and South ) with similar characteristics. To finalize questionnaires of perceived environmental risk based on these data were applied to these selected areas, in order to understand the degree of perception of the residents living in these most vulnerable neighborhoods

O dilema no momento atual de nossa sociedade é o desafio de como manter o desenvolvimento de novas tecnologias e que seja de maneira sustentável, porém, o desenvolvimento também acarreta impactos. Juntamente com o desenvolvimento vem o crescimento desordenado das cidades, causando danos tanto para o meio ambiente quando para a sociedade, fazendo-se necessários estudos sobre este tema e os consecutivamente os relacionados como vulnerabilidade ambiental e risco. O presente trabalho tem como objetivo a compreensão da questão da vulnerabilidade a riscos ambientais em áreas urbanas, analisando estes riscos em decorrência da variabilidade climática e a percepção aos riscos ambientais por parte dos moradores dos bairros mais vulneráveis do município de Marília (SP). Para a realização da pesquisa foi realizado levantamento bibliográfico acerca do tema e posteriormente para a delimitação da área de estudo dentro do município de Marília (SP) foram feitos uma interpolação de dados de Exclusão Social, Plano Diretor Municipal, Plano Local de Habitação de Interesse Social, Defesa Civil, chegando-se alguns bairros dentro de duas regiões (Nordeste e Sul) com características semelhantes. Para finalizar foram aplicados questionários de percepção de risco ambiental com base nesses dados nestas áreas escolhidas, visando entender o grau de percepção dos moradores que vivem nesses bairros mais vulneráveis
Keywords: Physical geography - Environmental aspects; Geografia física - Aspectos ambientais; Avaliação de riscos ambientais; Percepção geografica; Planejamento urbano; Marilia (SP)